Study of mild cognitive impairment by applying Kolkata cognitive screening battery in type 2 diabetes mellitus patients in India - Pednekar, Sangeeta; Karande, Shilpa; Parab, Madhura; Pandey, Dharmendra (International Journal of Research in Medical Sciences, 2017)
Background: Several prospective, large, population-based cohort studies have found that diabetes is associated with an increased risk of mild cognitive impairment (MCI). This study was aimed to determine the relationship between diabetes mellitus (DM) and MCI with respect to age of onset, duration, other co-morbidities, complications of diabetes and the effect of HbA1c on MCI, using Kolkata cognitive screening battery. Methods: From 1st December 2014 to 31st May 2015 a unicentric, case control study was designed to include patients attending the medicine outpatient clinic of LTMGH as per the inclusion and exclusion criteria. The cognition was assessed by Kolkata cognitive screening battery and the scores were compared with control subjects to rule out cognitive decline. A score below 110 was taken as the cut-off for identifying the significantly impaired. Results: 50 patients were included in study (mean age 57.02 years). The mean MCI score was 100.58 in the diabetic group, which was significantly less as compared to 123.35 as seen in the control group. Object naming test was the least affected. Furthermore, MCI had positive significant correlation (p<0.05) with nephropathy (p<0.05), retinopathy (p<0.05), HbA1c (p<0.05) and duration of DM (p<0.05). There was no significant co-relation between the sex of the patients and MCI (p>0.05). Conclusions: There is a strong correlation of MCI with HbA1c. This implies that control of diabetes may help improve cognition and help in better management of diabetes as MCI disrupts the individual’s lifestyle and interferes with day-to-day activities. The results of our study warrant future research to improve our understanding regarding MCI and its correlation with diabetes.